Malaysian Non-Governmental Organizations (NGOs) and humanitarian issues in Gaza, Palestine - Asmady Idris, (Institut Kajian Rantau Asia Barat, 2012)
Since Israel‟s blockade and the Operation Casting Lead (OCL)in the Gaza Strip, many international NGOs have come forward to render help and lessen the plight of the Palestinians. For the Malaysian NGOs, particularly Aman Palestin and Lifeline4Gaza, easing the burden of the Palestinians is a responsibility that must be shared. Although these two groups applied different approaches, with Aman Palestin using the land route of the Rafah crossing and the Lifeline4Gaza joining the international flotillas, the same goals are being pursued: to help the people of Palestine to be safe and free. To some extent, the rise of many NGOs in championing the issue of human rights at the international level has been considered as a challenge for the state. The continuous reaction of NGOs challenging the state on the issue of human rights has indirectly furthered the rivalry in the discipline of international relations, namely „state actor versus non-state actors (or NGOs)‟. Without relying on the influence of the powerful states, many international NGOs have successfully managed to show to the world that they can do things that states „cannot do‟. By using more diplomatic ways (delivering humanitarian aid), and not in the form of terrorism, this has been found to be more effective to tell the world leaders of the sufferings of the Gaza people. Nevertheless, in the case of Malaysia, it can be argued that both the state and non-state actors (Malaysian NGOs) are co-operating well in promoting the issue of human rights internationally. Both are supporting each other to ensure the mission and the vision of helping the Palestinians becomes a reality.